A New Approach to the Zero Subject in English - E. J. Ibragimova; T. V. Shulzhenko; A. А. Shumkov (Дискурс, 2022)
Introduction. For “subject question” it is traditionally presumed, that the subject in it is the interrogative word or word combination. From logical point of view it is not correct, because the subject in such sentence is not yet found, and the interrogative word or word combination just “help” in searching for it. In English, it is marked by different syntactic means, for example, by the absence of the auxiliary verb. Also in subject question a formal particle “there” shows up; however, its functions are still unclear. That is why the objective of this work is to build a formal logical model of subject in interrogative English sentence, including the searched subjects, without or with the particle “there”.Methodology and sources. The research methodology is based on the binomiality idea, having been developed since 1993 at ETU “LETI” by means of the method of formal-logical modelling. The examples illustrating the functional features of the searched subject in English interrogative sentence were selected by means of the method of continuous sampling from 7 corpora. Results and discussion. The diversity of subject structures in English interrogative sentence is considered, taking into account possible functions of the formal particle “there”. The assumption is supported, that the implicit subject is a “trace” of the explicit subject and may not be considered as the absolute zero subject. It is the searched subject, which is an absolute zero subject, i.e. an inexplicit one and it is necessary to initiate specifying the notion of the zero subject with distinction of implicit and inexplicit subjects.Conclusion. Out of dependence on its environment, the searched subject in English is an absolute zero subject, i.e. an inexplicit one. Most often it is a strong or weak vacant semifinitive, fixed in the weak specifier, or, rarer, a weak vacant semifinitive, fixed in the strong specifier. In interrogative sentences of English, no subject can be explicit or implicit when it is searched for; the auxiliary verb in the absence of emphasis or negation does not disappear, but is transformed into a flexion. In the structure of negative interrogative sentences one can see their enhanced (and, actually, maximum) energetics.